Bear Finds Eggs - Wilson, Karma; Chapman, Jane (New York : Margaret K. McElderry Books, 2024)
"As Bear and his friends stroll through the forest, they find different kinds of bird's eggs and leave gifts for the soon-to-be chicks."--
Keywords: Bears -- Juvenile fiction; Forest animals -- Juvenile fiction; Eggs -- Juvenile fiction; Stories in rhyme; Bears -- Fiction; Forest animals -- Fiction; Eggs -- Fiction; Stories in rhyme; Picture books